Pengaruh BI Rate, Jumlah Uang Beredar, Dan Nilai Tukar Terhadap Return Saham Property And Real Estate Tahun 2020 - 2022 - Dhias Pramudita Kusuma Wardani; Lailatul Maulida Azzahra; Siti Amaroh (JURNAL PUNDI, 2023)
This study aims to determine the level of the BI Rate, the money supply, and the exchange rate for sharia stock returns in property and real estate companies for the period 2020 - 2020. This research uses quantitative research. The population of this study used 53 property and real estatecompanies listed on the IDX for 2020 – 2022. The sample used a purposive sampling method with criteria including property and real estatecompanies listed on the IDX for 2020 – 2022 and have the required financial report data by this research variable in order to obtain a sample of 15 companies. The data sources obtained for this study are from the Indonesia Stock Exchange (IDX) and Bank Indonesia for 2020 – 2022. The results of this study partially show that the BI Rate variable and the Tupiah Exchange Rate against the dollar have no significant effect on stock returns and the money supply has a significant effect on stock returns. Meanwhile simultaneously the variables BI Rate, the money supply, the exchange rate of the rupiah against the dollar have a significant effect on stock returns.